Translating German philosophy into English: The case of Martin Heidegger - Arndt, Martin (Englisia Journal, 2021)
Language endangerment and language loss have become of focal interest for linguists and cultural anthropologists who bemoan the loss of linguistic diversity. The coinage of the term “linguicide” indicates the inherent problem that is related to mondialisation, universalization, and urbanization, which in itself is a highly controversial subject. The recent discoveries of Martin Heidegger’s black notebooks cast a new perspective on his work, revealing his revulsion at universalist ideologies and his antimodernism – and, most fatefully, his antisemitism: Jews who are to him the incarnation of rootlessness, distance from the soil, and thus subversion. Heidegger was born in a rural provincial German – and for many remained so, walking in the countryside, hating TV, airplanes, pop music, and processed food that all conspire to distract us from the basic wondrous nature of Being, overwhelming us with information, killing silence, and never leaving us alone, and thus keep us away from the confrontation with “das Nichts” (the Nothing), which lies on the other side of Being, that is, however, unknown to the chatter (das Gerede), which can be perceived in the newspapers, on TV and in the cities Heidegger hated to spend time in. Although he was a Nazi to the end, this does not mean that nothing can be learned from him or problems connected to his work. This library research deals with the complexity of translating this German philosopher into the English language. It draws not only on typical examples from Heidegger’s path-breaking philosophical work Sein und Zeit and presents attempts at translating it, but also points out their shortcomings and drawbacks. Additionally, it presents solutions to the problems that emerge from Heidegger’s idiosyncratic language. Generally speaking, it reveals the almost unbridgeable language barriers that can only be overcome at the expense of depth and authenticity. Homogenization can be seen as a way of leveling down ideas and concepts that end in language death.